WEEVIL ASSOCIATED TO GUMMOSIS IN OIL PALM (Elaeis guineensis Jacq.) IN BRAZIL - Moura, JosÃ© InÃ¡cio Lacerda; Oliveira, Marival Lopes de; Luz, Edna Dora Martins Newman; Silva, Stela Dalva Vieira Midlej; Santos, Rodrigo Souza (REVISTA DE AGRICULTURA, 2013)
In commercial plantations of oil palm in Nazare municipality, state of Bahia, Brazil, the association of Rhinostomus barbirostris Fabricius and Ceratocystis paradoxa (Dade) C. Moreau in high number of oil palm trees showing stem bleeding symptoms was observed. The pathogen was isolated from tissues of diseased oil palm plants. To our knowledge this is the first report on the contribution of R. barbirostris to increase the severity of stem bleeding disease caused by C. paradoxa in oil palm. Control measures are suggested.